RANCANG BANGUN APLIKASI MOBILE PERHITUNGAN ZAKAT MAAL BERBASIS ANDROID - Suhendri ST (PROCEEDING STIMA)
A growing phenomenon in Indonesian society today is lack of understanding on the implementation of one of the obligations that Muslims pay zakat maal. Our society often experience confusion about calculations, limits treasure that must be issued zakat and alms at the time should have been spent. Due to a lack of understanding of the charity society it is necessary tool to facilitate that seeks to make people in calculations, limits treasure that must be issued zakat and alms at the time should have been spent. The purpose of this study was to design and build mobile applications that contain the calculation of zakat maal. The expected benefits of the design of this application is easier for people to find out how much zakat maal must be issued based on the calculation set out in Islamic law. With the mobile application android based perhtiungan zakat maal then zakat maal calculation process can be done more quickly, easily and accurately. The problem of calculating zakat maal can be solved by this application in accordance with the provisions of Islamic law.Kata Kunci : Rancang Bangun, Aplikasi Mobile, Zakat Maal, Android.